The Evolution of Accounting as a Determinant of the Development of Financial Services - Świetla, Katarzyna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article looks at the centuries-old history of accounting, from ancient times up to the modern conditions prevailing in the global economy. The impact of accounting on the economy and feedback are shown. The article also stresses the need for accounting to be harmonised and the individuals engaged in it to become specialised so as to ensure that the information being presented is credible and a true picture of the company is put forth. The author also discusses the increasingly common use of knowledge and the involvement of companies providing specialist services to promote the desired quality of information from accounting while also reducing the cost of acquiring that information.